Cultural Theory, Political Ideology, and Burden Tolerance: The Role of Core Beliefs in Shaping Support for Administrative Burdens - Thomas Rabovsky; Matthew C. Nowlin; Emily Mee (The American Review of Public Administration, 2026)
Administrative burdens embedded within many public policies are often politically contentious, such that core values and belief systems can drive either support or opposition. In this paper, we use survey data from US respondents to replicate and extend previous research on the public acceptance of administrative burdens in general. First, we confirm the measure's validity by examining its effects on beliefs across policies that range from highly polarized to less politically contentious. Second, we test the relationship between tolerance of administrative burden and cultural theory (CT) variables that tap into worldview orientations related to hierarchy, egalitarianism, individualism, and fatalism, which previous research has found predictive of policy preferences across a wide range of domains, even after accounting for political ideology and partisanship. We hypothesize that egalitarians and individualists will generally be less tolerant of burdens, while hierarchs will be more accepting of burdensome requirements. However, this effect varies depending on the nature of the burdens and how they relate to perceived threats for each worldview.